Термоупругое состояние пластин, выполненных из различных материалов - Повгородний, В. О. (НТУ "ХПИ", 2009)
Розглянуто проблеми ідентифікації теплофізичних та механічних властивостей прямокутних пластинок. Наведено їх класифікацію та постанови. Також у даній статті розглядаються питання термопружності плит з пористих матеріалів.

The problems of the identification thermophysical and mechanical parameters of rectangular’s plates. Kvalifications are discussed. This article is devoted to the problem of thermoelasticity of the plate. Theses plates are constructed from the porous materials.
Keywords: модуль Юнга; коэффициент Пуассона; термоупругость; пористость; метод суперэлементов